The Management of Posttraumatic Nasal Deformities - Kao, W. Katherine; Ho, Tang (Facial Plastic Surgery, 2023)
Nasal bone fractures are the most common fractures of the facial skeleton and are often accompanied by bony, cartilaginous, and soft tissue injuries. These injuries are often complex, and when untreated or inadequately treated, can lead to posttraumatic nasal deformity. The most common deformities are the crooked nose and the saddle nose. Both deformities may result in significant cosmetic and functional concerns. The treatment of these deformities can be complex, requiring careful evaluation of the nose and thoughtful planning to correct the cosmetic deformity and restore functional integrity. The rhinoplasty surgeon will benefit from having a large repertoire of techniques to achieve these repairs. In this article, we discuss the options and concepts for the management of nasal bone fractures as well as complicated posttraumatic nasal deformity. Level of evidence is not available.
Keywords: posttraumatic nasal deformity; rhinoplasty; nasal bone fracture